(untitled) (Globalization and Business, 2023)
Technological progress and innovation go hand in hand with the history of human civilization. It has a profound effect on the development of modern life. EU institutions, along with national institutions of member and associate countries, as well as a growing number of international and global political institutions, are major sources of 21st-century formation. EU policy affects not only the lives of more than 500 million Europeans, but also global trends in areas such as climate change, resource utilization and sustainability, trade, healthcare, regional conflict resolution and poverty reduction. The aim of the paper is to show the trends of technological innovations that will play a big role in our lives in both the short and long term.